Redistributive Politics and the Tyranny of the Middle Class - Floris Zoutman; Bas Jacobs; Egbert Jongen (Center for Economic Studies and ifo Institute (CESifo), 2016)
The Netherlands has a unique tradition in which all major Dutch political parties provide CPB Netherlands Bureau for Economic Policy Analysis with highly detailed proposals for the tax benefit system in every national election. This information allows us to quantitatively measure the redistributive preferences of political parties. For each political party we calculate social welfare weights by income level using the inverse optimal-tax method. We find that all political parties roughly give a higher social welfare weight to the poor than to the rich. Furthermore, left-wing parties attach higher social welfare weights to the poor and lower social welfare weights to the rich than right-wing parties do. However, we also discover two anomalies. First, all political parties give a much higher social welfare weight to middle incomes than to the working and non-working poor. Second, all Dutch political parties attach a slightly negative social welfare weight to the rich by setting top rates beyond the revenue-maximizing `Laffer' rate. Finally, we detect a strong political status quo, since social welfare weights of all political parties hardly deviate from the welfare weights that are implied by the pre-existing tax-benefit system. We argue that political-economy considerations are key in understanding the political status quo and why middle-income groups are able to lower their tax burdens at the expense of both the low- and high-income groups.
Keywords: C63; D63; H21; 330; inverse optimal-tax method; revealed social preferences; political parties; optimal taxation; income redistribution